Pengembangan Butiran Premiks untuk Fortifikasi Zat Besi dalam Beras - Feri Kusnandar; Faleh Setia Budi; Yustikawati; Yane Regiyana; Slamet Budijanto (Jurnal Ilmu Pertanian Indonesia, 2020)
Iron-fortified rice potentially increases iron consumption in order to overcome anemia in Indonesia. Premix kernel can be applied as a fortificant vehicle being formulated into rice. The premix kernel is processed by mixing rice flour and iron source and extruded to yield rice-like extrudate. This research aimed to develop iron premix kernel using a double screw extruder and evaluate the fortificant homogeneity during mixing and stability due to washing as well as overall sensory acceptability of fortified rice. The premix kernel was made by mixing rice flour (1000 g), pyrophosphate ferries (containing 5,000 mg Fe), and GMS (10 g) for 5, 10, 15, 20, 25, and 30 minutes, added with water (450 mL) and passed into an extruder at 80°C. The dry-mixed for 20 minutes yielded a homogenous premix kernel (6,030±135 mg/kg with RSD of 2.25%). The mixing of premix kernel and Pandanwangi rice (1:100) for 25 minutes using a blade mixer yielded fortified rice with iron content of 39 mg/kg and RSD of 13.56%. The washing process of fortified rice decreased iron content, and the percentage of iron loss was affected by the washing frequency. Raw and cooked fortified rice did not differ organoleptically from those without fortification. Keywords: anemia, fortified rice, ferric pyrophospate, homogeneity, premix kernel